Advancing Radical Food Geographies Praxis through Participatory Film: Reflections from an Indigenous-Settler Food Sovereignty Collaboration - Levkoe, Charles Z.; Lowitt, Kristen; Furlotte, Sarah; Sayers, Dean (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
The academic field of geography is deeply embedded within capitalist and settler colonial logics and has played a major role in suppressing and concealing Indigenous histories along with rights claims, cultures, and practices. While geography’s origins are deeply problematic, over the past decades, many scholars and practitioners have offered counter theoretical and practical perspectives and approaches. Radical food geographies praxis is one such example that is rooted in engaged and socially relevant theory, practice, and reflection. In this article, we present reflections from our experience with radical food geographies research praxis through a collaborative food sovereignty, action-oriented project co-developed and co-led by two settler academics, a documentary filmmaker, and the Chief of Batchewana First Nation. From 2018-2022, we embarked on an effort to share stories of Batchewana First Nation’s historical and current fishing practices, culture, and governance through the co-creation of a feature length documentary film titled, Lake Superior Our Helper: Stories from Batchewanaung Anishinabek Fisheries (https://www.batchewanaungfish.ca). To write this paper, we engaged in a process of collective autoethnography that involved documenting our individual reflections on the project and then bringing these perspectives into dialogue. Emerging from this process, we share our insights for an engaged research praxis, focusing on meaningful and authentic relationships and partnership building, participatory film as a tool for collaborative research, and radical food geographies. We present these insights with the aim of improving our own individual and collaborative practice and to share our learnings with other scholars, activists, and community practitioners engaged in similar partnership-based and praxis-oriented geographic research.